(untitled) (Studia Prawnicze / The Legal Studies, 1969)
Autor artykułu porusza cywilnoprawną problematykę nieruchomości rolnych na obszarze miast i osiedli. Przedstawia historię formowania się sytuacji prawnej gruntów w miastach i osiedlach kiedy Polska znajdowała się pod zaborami i po odzyskaniu niepodległości. Autor analizuje obecnie obowiązujące regulacje prawne dotyczące nieruchomości rolnych na obszarze miast i osiedli. Przytacza m. in. przepisy kodeksu cywilnego, ustawy o gospodarce terenowej w miastach i osiedlach w zakresie obrotu i dziedziczenia, uchwały i rozporządzenia Rady Ministrów dotyczące gruntów rolnych na obszarach miast, ustawę z 1948 r. o podziale nieruchomości na obszarach miast i niektórych osiedli czy ustawę z 1961 r. o gospodarce terenami w zakresie dotyczącym użytkowania wieczystego. The author of this article addresses the civil law issue of agricultural property in urban and residential areas. He presents the history of the formation of the legal situation of land in towns and residential areas when Poland was under partition and after gaining independence. The author analyses the current regulations for agricultural property in urban and residential areas. He cites, inter alia, the provisions of the Civil Code, the Act on land management in towns and residential areas as regards turnover and inheritance, the resolutions and decrees of the Council of Ministers concerning agricultural land in urban areas, the Act of 1948 on the division of real estate in urban areas and certain residential areas or the Act of 1961 on the management of land as regards perpetual usufruct.